2023
DOI: 10.1161/jaha.122.029223
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Genotype Influences the Clinical Diagnosis of Familial Hypercholesterolemia

Abstract: Background Evidence suggests that LPA risk genotypes are a possible contributor to the clinical diagnosis of familial hypercholesterolemia (FH). This study aimed at determining the prevalence of LPA risk variants in adult individuals with FH enrolled in the Italian LIPIGEN (Lipid Transport Disorders Italian Genetic Network) study, with (FH/M+) or without (FH/M−) a causative genetic variant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These data suggest that high Lp(a) values may be a greater risk factor than carrying a genetic mutation causing heterozygous FH [ 79 ]. On the sidelines, we can mention that recently, the analysis of data from the LIPIGEN network in adults confirmed that very high Lp(a) levels can explain at least part of the clinical diagnoses of FH in subjects with very high-LDL cholesterol values and negative analysis for causative genes of this disease [ 80 ].…”
Section: Lp(a) In Children and Adolescentsmentioning
confidence: 99%
“…These data suggest that high Lp(a) values may be a greater risk factor than carrying a genetic mutation causing heterozygous FH [ 79 ]. On the sidelines, we can mention that recently, the analysis of data from the LIPIGEN network in adults confirmed that very high Lp(a) levels can explain at least part of the clinical diagnoses of FH in subjects with very high-LDL cholesterol values and negative analysis for causative genes of this disease [ 80 ].…”
Section: Lp(a) In Children and Adolescentsmentioning
confidence: 99%
“…In fact, a recent study conducted by the Italian network LIPIGEN showed that the correction of LDL-c levels for lipoprotein(a) levels resulted in a lower percentage of FH patients with LDL-c levels ≥190 mg/dL [14].…”
Section: Introductionmentioning
confidence: 99%